IT’s and competencies 2 (Journal of Parents and Teachers, 2014)
This article explains what the scientific competency is, what it is used for and it is within the competency in knowledge and interaction with the physic environment. This is the group of necessary abilities to understand the environment itself and the interaction between people through a scientific way of thinking, responsible attitude and improvement of health and environment. IT’s are necessary to develop this competency because they help keeping the enthusiasm for questions, stimulate individual and group work to deal with problems.
Keywords: new technologies; basic competencies; IT’s; scientific competency.